Inserting spaces before and after words affects word processing differently in Chinese: Evidence from eye movements. - Liu, Pingping; Li, Xingshan (British Journal of Psychology, 2014)
Unlike in English, there are no spaces between printed words in Chinese. In this study, we explored how inserting a space before or after a word affects the processing of that word in Chinese reading. Native Chinese readers' eye movements were monitored as they read sentences with different presentation conditions. The results show that inserting a space after a word facilitates its processing, but inserting a space before a word does not show this effect and inhibits the processing of that word in some cases. Our results are consistent with the prediction of a word segmentation and recognition model in Chinese Li et al., 2009, Cognit. Psychol., 58, 525. Additionally, we found that a space guides the initial landing position on the word: the initial landing position was further away from the space that inserted into the text, whether it was before or after a word.